Aneuploidy and oncoviruses. (12th August 2019) - Taheri, Fateme; Goudarzi, Hossein; Faghihloo, Ebrahim
Summary: Seven oncogenic viruses are known for tumorigenesis and contribute to 12% of all human cancers. The oncogenic factors, the target tissue, and pathology of cancer vary among these viruses with several mechanisms proposed for the initiation and development of cancer. Aneuploidy in cells is associated with anomalies in chromosome number that can be a hallmark of cancer, a disease defined by expanded proliferative potential. In this review, we summarize the different mechanisms of aneuploidy and furthermore discuss recent findings of the role of viral oncoproteins in inducing cellular aneuploidy that might facilitate tumorigenesis. Improved understanding of viral oncogenesis may help to find new strategies for controlling virus‐associated cancers.